The Influence of Working Posture on the Risk of Musculoskeletal Disorders in Batik Makers - Aranti, Wulan Adis; Sumardiyono; Murti, Bhisma (Indonesian Journal of Medicine, 2024)
Background: Complaints of musculoskeletal disorders (MSDs) such as feelings of pain, soreness or soreness in the skeletal muscles felt by batik makers both during work and after work. This study aimed to examine the influence of work posture on the risk of MSDs in batik craftsmen. Subjects and Method: This was a cross-sectional study. Total sample was 200 batik craftsmen was selected by cluster random sampling. The dependent variables were pain and musculoskeletal disorders. The independent variables were age, work posture, work duration, work period, and type of batik craftsmen. Pain was measured using visual analog scale (VAS). MSDs was measured using the Nordic Body Map (NBM). Other variables were collected using questionnaire. The data were analyzed using a multiple logistic regression. Results: Batik craftsmen with non-ergonomic working postures (OR= 2.98; 95% CI=1.27 to 6.99; p= 0.012), age ≥40 years old (OR= 3.45; 95% CI=1.28 to 10.49; p= 0.015), works ≥5 hours/day (OR= 3.52; 95% CI= 1.46 to 8.47; p= 0.012), tenure ≥5 years (OR= 7.04; 95% CI= 3.00 to 16.53; <0.001) significantly increased the risk of MSDs. There was no significant association between type of batik craftsmen and MSDs (OR= 2.76; 95% CI= 0.81 to 9.38; p= 0.102). Nagelkerke R2= 30.8%. Conclusion: Non-ergonomic working postures, age ≥40 years old, works ≥5 hours/day, tenure ≥5 years significantly increase the risk of MSDs. There is no significant association between type of batik craftsmen and MSDs. Keywords: musculoskeletal disorder, pain, work duration, work period, age, batik making